Design of low-power analog filters in WBAN receiver front-ends for hyper/hypothyroidism patients - Wang, Xiaoying (Nanyang Technological University, 2022)
The rapid growth in wireless communication technology and semiconductor industry has brought revolutionary changes and advanced solutions for healthcare providers. Recently, continuous efforts have been made in building integrated complementary metal–oxide–semiconductor (CMOS) wireless transceivers with lower power and lower cost. These cutting edge wireless solutions have empowered the healthcare market thanks to the emerging development of Wireless Body Area Network (WBAN). WBAN constitutes an active research topic which offers the potential in improving the quality of service for various healthcare services. Healthcare providers may monitor and record patients' physiological data and various vital signs by taking advantages of the wireless communication system and heterogeneous biological sensors. Besides, WBAN constructs a secured communication channel between doctor and patient to ensure the timely delivery of proper diagnosis. Hyperthyroidism and hypothyroidism are two chronic endocrine diseases related to the abnormal function of the thyroid gland. These thyroid-related disorders are commonly seen globally, which affect patients' basic metabolism. Patients may exhibit symptoms such as irregular heart beat, depression, muscle weakness, thyroid gland enlargement and so on. Healthcare provides treat such diseases so that the thyroid hormone levels return to normal. However, overdosing the medication may lead to the reversion of the hormone levels and hence would worse the effect of treatment. Therefore, the WBAN devices are necessary to undertake the monitoring task for hyper/hypothyroidism patients. This thesis aims at providing the active filter solution for the WBAN transceiver devices. In a complete WBAN system, multiple communication standards are embedded to allow communications between or within different stages. Active filters are the key building blocks that ensure effective communications. With the fast developing speed of the wireless communication technology, WBAN system has raised the requirements for high performance filters. The Institute of Electrical and Electronics Engineers (IEEE) 802.15.6 standard for WBAN systems states that the WBAN filters need to deal with weak signals where interference matters and distort the integrity. Therefore, high passband selectivity, low signal distortion, low noise and high linearity performance are the stringent requirements for such active filters. In this thesis, we would propose different active filter designs to meet the power and linearity requirement for the WBAN system. Firstly, a novel LPF design adopts the transconductor-C (Gm-C) topology where the linearity of the transconductor is enhanced using the regulated cascode technique. Adopting the level shifter and additional gain stage allows the continuous tuning of the transconductance value and hence the cutoff frequency. Secondly, another Gm-C topology utilizes the source-follower structure to generate the linear transconductance is presented. The source-follower includes less active elements as compared to the first design and hence achieves better linearity performance. However, it produces fixed transconductance so the cutoff frequency can only be discretely adjusted with external programmable capacitor array. Moreover, we have also explored another source-follower-based biquadratic filter design. Instead of employing the Gm-C topology, a single source-follower-based cell can produce second-order biquadratic frequency response. Two biquadratic cells are cascaded to build a fourth-order Butterworth low-pass frequency response. Simulations and measurements have been carried out on each design to evaluate the passband tunability and the linearity performance. A figure-of-merit (FoM) was also introduced to compare the power efficiency and the linearity performance together with the noise performance. Last but not least, the conclusion is drawn in the end of this thesis with future work which may include the flipped-source-follower cell to deal with the trade-off between the noise performance and the in-band linearity.